Reviews in fluorescence 2010 - Geddes, Chris D. (Reviews in fluorescence, 2012)
Reviews in Fluorescence 2010, the seventh volume of the book serial from Springer, serves as a comprehensive collection of current trends and emerging hot topics in the field of fluorescence and closely related disciplines. It summarizes the year's progress in fluorescence and its applications, with authoritative analytical reviews specialized enough to be attractive to professional researchers, yet also appealing to the wider audience of scientists in related disciplines of fluorescence. Reviews in Fluorescence offers an essential reference material for any lab working in the fluorescence field and related areas. All academics, bench scientists, and industry professionals wishing to take advantage of the latest and greatest in the continuously emerging field of fluorescence will find it an invaluable resource.  Key features: • Accessible utility in a single volume reference. • Chapters authored by known leading figures in the fluorescence field. • New volume publishes annually. • Comprehensive coverage of the year's hottest and emerging topics. Reviews in Fluorescence 2010 topics include: • Novel Metal-based Luminophores for Biological Imaging. • Hydration Dynamics of Probes and Peptides in Captivity. • How does tobacco etch viral mRNA get translated? A fluorescence study of competition, stability and kinetics. • Synchronous Fluorescence Spectroscopy and Its Applications in Clinical Analysis and Food Safety Evaluation. • Quantitative molecular imaging in living cells via FLIM. • A Multiparametric Imaging of Cellular Coenzymes for Monitoring Metabolic and Mitochondrial Activities. • Optimal Conditions for Live Cell Microscopy and Raster Image Correlation Spectroscopy (RICS).